2011
DOI: 10.2215/cjn.00670111
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Levels and All-Cause and Cardiovascular Mortality in the Hemodialysis Population

Abstract: SummaryBackground and objectives Hyperuricemia is associated with hypertension, coronary artery disease, and chronic kidney disease. However, there are no specific data on the relationship of uric acid to cardiovascular disease in the chronic hemodialysis setting.Design, setting, participants, & measurements Data from 5827 patients on chronic hemodialysis from six countries affiliated with the Dialysis Outcomes and Practice Patterns Study (DOPPS) were analyzed. All laboratory data were based upon the initial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
126
3
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(148 citation statements)
references
References 29 publications
16
126
3
3
Order By: Relevance
“…128 Another large retrospective study involving 5827 HD patients reported that higher serum UA levels were correlated with lower risk of allcause and CVD mortality. 13 These results might be explained by the reverse epidemiology. Interestingly, from ancient times, it was well known that gout was a disease of the Emperors of the Byzantium suggesting their better socialeconomic status compared with malnourished people.…”
Section: Hua and CV Mortalitymentioning
confidence: 98%
See 1 more Smart Citation
“…128 Another large retrospective study involving 5827 HD patients reported that higher serum UA levels were correlated with lower risk of allcause and CVD mortality. 13 These results might be explained by the reverse epidemiology. Interestingly, from ancient times, it was well known that gout was a disease of the Emperors of the Byzantium suggesting their better socialeconomic status compared with malnourished people.…”
Section: Hua and CV Mortalitymentioning
confidence: 98%
“…The impact of UA in all-cause and CV mortality of dialysis patients' remains controversial. 12,13 Controversial also remains the role of UA in renal transplantation. 7 Relationship of HUA -chronic kidney disease incidence and progression Several studies with conflicting results in some instance have investigated the relationship between HUA and CKD.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, hyperuricemia has been shown to be associated with an increased risk of hypertension (8,9), prehypertension (10), peripheral arterial disease (11), diabetes mellitus (12), CKD (13), and cardiovascular disease (CVD) (8,10,14). Conversely, in the HD population, hyperuricemia has been shown as a good nutritional marker (15) that can also predict lower rates of upcoming hospitalizations (15) as well as lower all-cause and cardiovascular death risks (15,16). Although the data about the mortality predictive role of higher SUA levels in the HD population are somewhat controversial (3,4,(15)(16)(17)(18), most of the studies conducted on this topic presented low SUA as a mortality risk factor in patients on MHD (3,4,15,16,18).…”
Section: Introductionmentioning
confidence: 99%
“…A similar mechanism might explain the apparent protective effect of hyperuricemia on patients with end-stage renal disease, who are on hemodialysis. Higher SUA has been shown previously to be associated with lower risk of all-cause mortalities and CV deaths [7].…”
Section: Introductionmentioning
confidence: 87%